A Comparative Study on Efficacy of 30% Trichloroacetic Acid versus 35% Glycolic Acid Peel in the Treatment of Melasma (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Melasma is a common hyperpigmented disorder of skin which has severe impact on the quality of life. Many modalities of treatment are available to treat melasma. Among them chemical peeling is one of the most popular and widely used method of treatment for melasma.Objective: The present study was aimed to assess the efficacy of 30% trichloroacetic acid versus 35% glycolic acid peel in the treatment of melasma.Materials and Methods: The prospective randomized study included 50 patients of melasma of both sexes, in 20-55 years age group. Patients were randomly divided into two equal groups A and B. Group A was treated with trichloroacetic acid (TCA 30%) peel and group B with glycolic acid (GA 35%) peel. Five peels were done serially at intervals of 21 days. Patients were followed up every 3 weekly for 6 weeks after the last peel. The disease severity was monitored with digital photography and melasma area and severity index (MASI) score which were calculated at baseline, 6 weeks, 12 weeks and 18 weeks. A visual analog scale (VAS) was calculated at baseline, 12 weeks and 18 weeks.Results: Glycolic acid showed better response compared to trichloroacetic acid at the end of five peels, but this difference was not statistically significant (p>0.05). Chemical peeling with trichloroacetic acid produced significantly more erythema, burning sensation (p